PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN YANG DIMODERASI OLEH MOTIVASI KERJA PADA BPR SE-KECAMATAN SUKAWATI GIANYAR - GEDE, KOMANG GD; Priartini, Putu Saroyeni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018, 2018)
Performance can be known and measured if an individual or group of employees has the criteria or standard of success of the benchmarks set by the organization. This research was conducted in all BPR (Bank Perkreditan Rakyat) in Sukawati District Gianyar which engaged in banking. The number of samples using slovin method is 68 respondents. Analysis results can be seen that leadership has a positive and significant impact on employee performance. Motivation of work has a positive and significant impact on employee performance. Work motivation moderates the influence of leadership positively and significantly on employee performance. Suggestions that can be given, the BPR leaders in Gianyar Regency should clearly provide the attitude that is considered good by subordinates, competent in providing tasks, such as the suitability of tasks with the ability of employees to produce good performance. In motivating employees every leader should instill positive attitude of employees to the work they receive, such as the attitude of responsibility and teach that all work given immediately be completed to achieve good results as employee motivation in improving the performance in the company, so that employees have the ability to overcome the problems it faces to show good performance.